Kinematic analysis of classical skiing technique in sprint for young and adult athletes - Novikova, N. B.; Belyova, A. N.; Ivanova, I. G.; Kotelevskaya, N. B. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to determine the features of the kinematics of the alternating two-step course of young athletes at a sprint distance and to compare the angular characteristics of the main phases of the course with the indicators of the strongest athletes in the world.